Hydrothermal alterations in geological exploration by Skarn Copper-Zinc deposits - Rodríguez Delgado, Mario Dominico (2022)
Skarn-type deposits show complex mineralogical and textural relationships because of the variety of geological processes involved in their development. Mineral associations can be further complicated by supergene leaching and oxidation. Consequently, hydrothermal alterations constitute complex geochemical signatures to be analysed under a number of factors in these mineralised systems, which are conclusive in vectoring these types of deposits. This study is proposed in order to understand these alterations and to propose their usefulness in the exploration of Cu-Zn skarn deposits. The methodology of bibliographic research and case studies was used, from three main sources of data: information from the Mesozoic sedimentary belt of the Inter-Andean Cordillera and the Yauli dome, case studies from different parts of the world and analysis of the geological, magmatic and petrological conditions of their formation. The analysis of the data in accordance with the research design, allows to establish results such as: the characterization of a Cu-Zn skarn, definition of its geological and tectonic environment, spatial location and mineral zoning defined by geochemical halos, which highlight the importance and usefulness of hydrothermal alterations in the location of these mineral deposits.